MEMBANGUN PARADIGMA PENDIDIKAN AGAMA ISLAM YANG INKLUSIF DAN MODERAT DALAM KONTEKS TUNAGRAHITA: Building an Inclusive and Moderate Islamic Education Paradigm in the Context of Tunagrahita - Yuan Remanita; Aqilul Fathoni, Irgi; Junaris, Imam (STAI Ma'had Aly Al-Hikam Malang, 2025)
Islamic Education plays an important role in instilling character, morals, and spiritual values in students, including children with special needs in special schools. For students with intellectual disabilities, Islamic Religious Education material, which tends to be abstract, is often difficult to understand. Hence, teachers need to apply learning strategies that are simpler, more concrete, and appropriate to their abilities. This study used a qualitative approach with a case study method at the SLB Negeri Campurdarat. Data were collected through interviews, observations, and documentation involving Islamic education teachers, classroom teachers, the principal, students, and parents. The results showed that teachers adapted the material to make it easier to understand, used multisensory methods, and instilled tolerance through role modeling, social habits, and daily practices. The obstacles that arise include students' cognitive limitations, lack of supporting facilities, and lack parental involvement. This study is still limited to one location, so the findings cannot be generalized and do not describe long-term developments. These findings encourage the need for policy support in the form of special Islamic education modules for students with special needs and teacher training to integrate the values of religious moderation. Pendidikan Agama Islam berperan penting dalam menanamkan karakter, akhlak, dan nilai spiritual peserta didik, termasuk pada anak berkebutuhan khusus di sekolah luar biasa. Bagi siswa tunagrahita, materi PAI yang cenderung abstrak sering sulit dipahami, sehingga guru perlu menerapkan strategi pembelajaran yang lebih sederhana, konkret, dan sesuai dengan kemampuan mereka. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus di SLB Negeri Campurdarat. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi yang melibatkan guru PAI, guru kelas, kepala sekolah, siswa, serta orang tua. Hasil penelitian menunjukkan bahwa guru menyesuaikan materi agar lebih mudah dipahami, menggunakan metode multisensori, serta menanamkan sikap toleransi melalui keteladanan, pembiasaan sosial, dan praktik sehari-hari. Kendala yang muncul antara lain keterbatasan kognitif siswa, minimnya sarana pendukung, dan kurangnya keterlibatan orang tua. Penelitian ini masih terbatas pada satu lokasi sehingga temuan belum bisa digeneralisasi, dan belum menggambarkan perkembangan jangka panjang. Temuan ini mendorong perlunya dukungan kebijakan berupa modul PAI khusus bagi siswa berkebutuhan khusus serta pelatihan guru untuk mengintegrasikan nilai moderasi beragama. Kata Kunci : Inklusif; Moderat; Paradigma; Pendidikan Agama Islam; Tunagrahita.